Dragon Trouble - "Lively, Penelope" (Mammoth: London, 1999)
Peter wants to give his grandfather something special for his birthday: something different and unusual. But when the ideal present hatches into dragons, Peter and his grandfather are in for more trouble than they could ever imagine.
Keywords: Cornwall Juvenile-English Fiction